2021
DOI: 10.1021/acsabm.1c00108
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Transcriptome Responses to Environmental Stresses in Agricultural Crops Treated with Carbon-Based Nanomaterials

Abstract: Carbon-based nanomaterials (CBNs) such as carbon nanotubes (CNTs) and graphene can be beneficial to crops exposed to abiotic stresses such as drought and high salinity. Our findings suggest that the improvement observed in stressed crops treated with CBNs can be associated with CBN-induced restoration of gene expression. When subjected to salt stress, sorghum seedlings showed modified expression in 51 stressrelated genes. The introduction of CNTs or graphene into the salty growth medium resulted in the restora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This study indicates that NP treatment of plants under drought stress induced tolerance by regulating the gene expression of drought-related genes and promoting the biosynthesis of ABA (Linh et al 2020 ). Transcriptomic studies have revealed that CNTs can upregulate stress-related genes in both monocotyledonous and dicotyledonous plants (Rezaei Cherati et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…This study indicates that NP treatment of plants under drought stress induced tolerance by regulating the gene expression of drought-related genes and promoting the biosynthesis of ABA (Linh et al 2020 ). Transcriptomic studies have revealed that CNTs can upregulate stress-related genes in both monocotyledonous and dicotyledonous plants (Rezaei Cherati et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…This suggests the potential application of CNMs in alkaline soil. The suitability of CNMs in saline‐alkali farmland has been demonstrated, Cherati et al (2021) demonstrated that CNMs (such as carbon nanotubes and graphene) can modify crops gene expression that are exposed to abiotic stresses, including drought and high salinity conditions. Khodakovskaya et al (2013) proposed that modulating the surface charge of CNMs can impact the expression of water channel protein genes and crop growth in tomatoes.…”
Section: Discussionmentioning
confidence: 99%
“…Tomato seeds obtained from Reimer Seeds Co. Inc. (Saint Leonard, MD, USA) were sterilized as before. 16 Sterile seeds were placed in small germination pots and incubated in a growth chamber for 21 days with the following conditions: 24 °C, 12 hours of light with a light intensity of 105 μmol s −1 m 2 . At the end of the germination period, 3 week-old tomato seedlings were transferred to experimental pots containing ∼400 g of Sun Gro Redi-earth Plug and Seedling Mix soil (Sun Gro Horticulture, Inc.) for exposure experiments.…”
Section: Plant Cultivation and Cnm Exposure Experimentsmentioning
confidence: 99%
“…13,14 Transcriptomics analysis revealed that graphene induced upregulation of transcriptional factors, plant hormone signal transduction, nitrogen and potassium metabolism, and secondary metabolism in maize roots. 15 More recently, Rezaei Cherati et al (2021) found that CNTs and graphene enhanced tolerance to salinity and drought in tomato, rice, and sorghum by reconciling the expression of affected stressresponsive genes, including those encoding transcription/ translation factors, dehydrins, heat shock proteins and aquaporins, and genes involved in calcium transport, mitogen-activated protein kinase (MAPK) signaling cascade, abscisic acid metabolism and signaling. 16 The same study further found that CNTs restored more genes than graphene in tomato seedlings under salinity stress, while graphene restored more genes than CNTs in rice under drought stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation